2005
DOI: 10.1038/ng1655
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in selenoprotein S influences inflammatory response

Abstract: Chronic inflammation has a pathological role in many common diseases and is influenced by both genetic and environmental factors. Here we assess the role of genetic variation in selenoprotein S (SEPS1, also called SELS or SELENOS), a gene involved in stress response in the endoplasmic reticulum and inflammation control. After resequencing SEPS1, we genotyped 13 SNPs in 522 individuals from 92 families. As inflammation biomarkers, we measured plasma levels of IL-6, IL-1beta and TNF-alpha. Bayesian quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
302
4
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 344 publications
(314 citation statements)
references
References 32 publications
6
302
4
2
Order By: Relevance
“…Variations in the SEPS1 gene are associated with the circulating levels of inflammatory cytokines IL-1b, IL-6 and TNF-a. 34 A recent study conducted in two independent Finnish cohorts indicated that variation in the SEPS1 locus may have an effect on cardiovascular disease morbidity, especially in females. 35 Our results seem to suggest the involvement of SEPS1 as host factor that might be also involved in determining the individual susceptibility to AgP.…”
Section: Resultsmentioning
confidence: 99%
“…Variations in the SEPS1 gene are associated with the circulating levels of inflammatory cytokines IL-1b, IL-6 and TNF-a. 34 A recent study conducted in two independent Finnish cohorts indicated that variation in the SEPS1 locus may have an effect on cardiovascular disease morbidity, especially in females. 35 Our results seem to suggest the involvement of SEPS1 as host factor that might be also involved in determining the individual susceptibility to AgP.…”
Section: Resultsmentioning
confidence: 99%
“…200 A particular polymorphism of SelS was proven to be responsible for increased plasma level of the inflammatory cytokines. 201 A possible increased risk of several inflammatory diseases could be the consequence, but a direct correlation with stroke, autoimmune disorders or inflammatory bowel disease is still not proven. 188 As a whole, Se participates in the immune response through several actions: it regulates the balance of activity in the eicosanoid synthesis pathways, leading to preferential synthesis of leukotrienes and prostacyclins over thromboxanes and prostaglandins, and down-regulates cytokine and adhesion molecule expression.…”
Section: Immune Defence and Inflammatory Disordersmentioning
confidence: 99%
“…Reporter gene experiments indicate that the SNP have functional consequences. Second, SelS is another selenoprotein recently found to have a function in the ER stress response (33)(34)(35) . An SNP in the SELS promoter at position -105 is regarded as being functionally significant as it modulates levels of inflammatory markers such as TNF-a and interleukin (33) .…”
Section: Functional Single-nucleotide Polymorphisms In Sels and Othermentioning
confidence: 99%
“…Second, SelS is another selenoprotein recently found to have a function in the ER stress response (33)(34)(35) . An SNP in the SELS promoter at position -105 is regarded as being functionally significant as it modulates levels of inflammatory markers such as TNF-a and interleukin (33) . Third, SNP have been identified in the promoter region of the GPX3 gene coding for the plasma glutathione peroxidase GPx3 and gene reporter experiments suggest that these affect promoter activity (36,37) .…”
Section: Functional Single-nucleotide Polymorphisms In Sels and Othermentioning
confidence: 99%